2006
DOI: 10.1016/j.pbb.2006.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of 5-HT2A/C receptors and DOI-induced behaviors by protein kinase Cγ

Abstract: Protein kinase C γ (PKCγ) null mutant mice demonstrate increased behavioral impulsivity and ethanol consumption. Pharmacological studies have shown that 5-HT 2A/C receptors modulate impulsivity and ethanol consumption in rodents and that PKC can regulate 5-HT 2A/C receptors. To determine whether PKCγ plays a selective role in 5-HT 2A/C receptor regulation, biochemical and behavioral experiments were performed in PKCγ mutant and wild-type mice. DOI-stimulated phosphoinositol hydrolysis and [ 125 I]-DOI saturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
(55 reference statements)
2
8
0
Order By: Relevance
“…Keeping in mind that staurosporine did not seem to augment the extracellular 5‐HT levels (no effect in both electrophysiological recordings and HTR paradigm), we can hypothesize that protein kinase blockade led to an enhanced sensitivity/responsiveness of some 5‐HT receptors in response to the 5‐HT elevation produced by escitalopram. This hypothesis is in line with results showing that the HTR is increased in PKC‐gamma null mutant mice compared to wild‐type littermate controls after an injection of 5‐HT2A/C receptor agonist, 2,5‐dimethoxy‐4‐iodoamphetamine (DOI), probably related to increased 5‐HT2A/C receptor responsiveness . Similar to our electrophysiological data, staurosporine prevented the attenuating effect of R‐citalopram on escitalopram action on L‐5‐HTP‐induced HTR paradigm.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Keeping in mind that staurosporine did not seem to augment the extracellular 5‐HT levels (no effect in both electrophysiological recordings and HTR paradigm), we can hypothesize that protein kinase blockade led to an enhanced sensitivity/responsiveness of some 5‐HT receptors in response to the 5‐HT elevation produced by escitalopram. This hypothesis is in line with results showing that the HTR is increased in PKC‐gamma null mutant mice compared to wild‐type littermate controls after an injection of 5‐HT2A/C receptor agonist, 2,5‐dimethoxy‐4‐iodoamphetamine (DOI), probably related to increased 5‐HT2A/C receptor responsiveness . Similar to our electrophysiological data, staurosporine prevented the attenuating effect of R‐citalopram on escitalopram action on L‐5‐HTP‐induced HTR paradigm.…”
Section: Discussionsupporting
confidence: 92%
“…Despite having no effect by itself on HTR, R-citalopram significantly diminished the escitalopram-induced increase of head twitches, in accordance with previous studies [6,37]. Furthermore, staurosporine had no effect by itself on this parameter, which concords with data showing no difference in the number of HTR in PKC-gamma null mutant versus wild-type mice [41]. However, staurosporine potentiated the HTR enhancement induced by escitalopram.…”
Section: Discussionsupporting
confidence: 91%
“…Mice lacking the neuronal specific, PKCγ, show enhanced DOI-induced phospholipase C activation and increased number of DOI-induced HTRs, suggesting a suppressive effect of PKCγ on DOI-mediated intracellular functions. [201] Importantly PKCγ knockout mice do not show alterations in brain 5-HT 2A receptor density. [201] …”
Section: Neural and Cellular Systems Underlying The Psychoactive Effementioning
confidence: 99%
“…[201] Importantly PKCγ knockout mice do not show alterations in brain 5-HT 2A receptor density. [201] …”
Section: Neural and Cellular Systems Underlying The Psychoactive Effementioning
confidence: 99%
“…In addition, the Ser and Thr mutagenesis data do not rule out the involvement of atypical PKC members or noncanonical PKC phosphorylation sites. Recent studies showed that PKCγ knockout elevates 5-HT 2A signaling in vivo as DOI-induced head twitch responses are significantly elevated by PKCγ knock-out, effects that are not due to changes in receptor number or agonist affinity (Bowers et al, 2006). Other recent studies suggest that calmodulin (CaM) also interacts with 5-HT 2A at consensus CaM binding motifs in intracellular loop 2 and the carboxy-terminal tail in a calcium dependent manner (Turner and Raymond, 2005).…”
Section: Introductionmentioning
confidence: 99%